2021
DOI: 10.1002/ps.6530
|View full text |Cite
|
Sign up to set email alerts
|

A conditional female lethal system for genetic suppression of the global fruit crop pest Drosophila suzukii

Abstract: BACKGROUND Drosophila suzukii (Matsumura, 1931, Diptera: Drosophilidae) is a global pest of soft‐skinned fruits such as blueberries, cherries and raspberries. Also known as spotted‐wing drosophila, D. suzukii is native to Asia but is now widely distributed in the Americas and Europe, and presents a serious challenge for growers. Genetic control strategies offer an environmentally friendly approach for the control of D. suzukii. RESULTS In this study, we developed transgenic strains of D. suzukii that carry dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…In this study, the FL19 transgene reported recently (Li et al, 2021) was remobilized to new locations on the third and X chromosomes. As expected, the third chromosome jumps were relatively short with the most distant transgene less than 70 kb a Total count of offspring from three independent vials of flies except for the homozygous chromosome 3 and X + FL19 lines where the data is from the productivity experiment shown in from the original FL19 location.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In this study, the FL19 transgene reported recently (Li et al, 2021) was remobilized to new locations on the third and X chromosomes. As expected, the third chromosome jumps were relatively short with the most distant transgene less than 70 kb a Total count of offspring from three independent vials of flies except for the homozygous chromosome 3 and X + FL19 lines where the data is from the productivity experiment shown in from the original FL19 location.…”
Section: Discussionmentioning
confidence: 95%
“…The relative humidity in the lab was between 20% and 50% and the lights were on for about 12 h on most days. The original wild-type colony was established from infested fruit collected from a field in North Carolina in 2011 ( Burrack et al, 2013 ) and the initial FL19 strain was previously made by piggyBac -mediated germline transformation of this wild type strain ( Li et al, 2021 ). The wild type colony was periodically genetically augmented with flies collected in North Carolina ( Elsensohn et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations